1865-66 N.C. Sess. Laws 33-34, Pub. Laws, ch. 21, § 11 - (:unkn) unknown (General Publisher, 1866)
Imposed a $1 tax on every dirk, Bowie knife, pistol, sword cane, dirk cane, and rifle cane used or worn during the year.
--
Keywords: TAX - PROPERTY OR SALES